The Multirole of Liposomes in Therapy and Prevention of Infectious Diseases - Nisini, Roberto; Poerio, Noemi; Mariotti, Sabrina; De Santis, Federica; Fraziano, Maurizio (Frontiers in Immunology, 2018)
Liposomes are closed bilayer structures spontaneously formed by hydrates phospholipids that are widely used as efficient delivery systems for drugs or antigens, due to their capability to encapsulate bioactive hydrophilic, amphipathic and lipophilic molecules into inner water phase and/or within lipid leaflets. The efficacy of liposomes as drug or antigen carriers has been improved in the last years to ameliorate pharmacokinetics and capacity to release their cargo in selected target organs or cells. Moreover, different formulations and variations in liposome composition have been often proposed to include immunostimulatory molecules, ligands for specific receptors or stimuli responsive compounds. Intriguingly, independent research has unveiled the capacity of several phospholipids to play critical roles as intracellular messengers in modulating both innate and adaptive immune response through various mechanisms, including i) activation of different antimicrobial enzymatic pathways, ii) driving the fusion-fission events between endosomes with direct consequences to phagosome maturation and/or to antigen presentation pathway, and iii) modulation of the inflammatory response. These features can be exploited by including selected bioactive phospholipids in the bilayer scaffold of liposomes. This would represent an important step forward since drug or antigen carrying liposomes could be engineered to simultaneously activate different signal transduction pathways and target specific cells or tissues to induce antigen specific T and/or B cell response. This lipid-based host-directed strategy can provide a focused antimicrobial innate and adaptive immune response against specific pathogens and offer a novel prophylactic or therapeutic option against chronic, recurrent or drug-resistant infections.